Sex differences in frailty: A systematic review and meta-analysis - Gordon, E.H.; Peel, N.M.; Samanta, M.; Theou, O.; Howlett, S.E.; Hubbard, R.E. (Experimental gerontology, 2017)
It is a well-described clinical phenomenon that females live longer than males, yet tend to experience greater levels of co-morbidity and disability. Females can therefore be considered both more frail (because they have poorer health status) and less frail (because they have a lower risk of mortality). This systematic review aimed to determine whether this ageing paradox is demonstrated when the Frailty Index (FI) is used to measure frailty. Medline, EMBASE and CINAHL databases were searched for observational studies that measured FI and mortality in community-dwellers over 65years of age. In five-year age groups, meta-analysis determined the sex differences in mean FI (MD=mean FIfemale−mean FImale) and mortality rate. Of 6482 articles screened, seven articles were included. Meta-analysis of data from five studies (37,426 participants) found that MD values were positive (p<0.001; MD range=0.02–0.06) in all age groups, indicating that females had higher FI scores than males at all ages. This finding was consistent across individual studies. Heterogeneity was high (I2=72.7%), reflecting methodological differences. Meta-analysis of mortality data (13,127 participants) showed that male mortality rates exceeded female mortality rates up until the 90 to 94-years age group. Individual studies reported higher mortality for males at each level of FI, and higher risk of death for males when controlling for age and FI. The pattern of sex differences in the FI and mortality of older adults was consistent across populations and confirmed a ‘male-female health-survival paradox’. •The male-female health-survival paradox: females live longer than males but with poorer health.•Studies using the Frailty Index (FI) consistently show that at any given age, females have higher FI scores than males.•Females tolerate this frailty better, as demonstrated by a lower mortality rate at any given FI score or age.•The FI model provides a framework for investigating the mechanisms that underpin this sex paradox.